2016
DOI: 10.1038/srep23170
|View full text |Cite
|
Sign up to set email alerts
|

miR-33-5p, a novel mechano-sensitive microRNA promotes osteoblast differentiation by targeting Hmga2

Abstract: MicroRNAs (miRNAs) interfere with the translation of specific target mRNAs and are thought to thereby regulate many cellular processes. However, the role of miRNAs in osteoblast mechanotransduction remains to be defined. In this study, we investigated the ability of a miRNA to respond to different mechanical environments and regulate mechano-induced osteoblast differentiation. First, we demonstrated that miR-33-5p expressed by osteoblasts is sensitive to multiple mechanical environments, microgravity and fluid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 68 publications
2
78
0
Order By: Relevance
“…In particular, HMGA2 was a concern among those potential targets, as it has been reported that miR-33-5p promotes osteoblast differentiation by targeting HMGA2 [20]. Also, HMGA2 is associated with highly proliferating human bone marrow-derived mesenchymal stem cells and plays a role in bone formation [21].…”
Section: Resultsmentioning
confidence: 99%
“…In particular, HMGA2 was a concern among those potential targets, as it has been reported that miR-33-5p promotes osteoblast differentiation by targeting HMGA2 [20]. Also, HMGA2 is associated with highly proliferating human bone marrow-derived mesenchymal stem cells and plays a role in bone formation [21].…”
Section: Resultsmentioning
confidence: 99%
“…36,38,39 To confirm the microgravity achieved by this clinostat, we tested the effects of the simulated microgravity on biological characteristics of primary mouse osteoblasts in this experimental condition ( Figure S1). The clinostat (Astronaut Research and Training Center, China) is an effective tool to simulate microgravity.…”
Section: Clinorotation To Simulate Microgravitymentioning
confidence: 99%
“…The chambers were divided into two groups: horizontal rotation control and clinorotation. 36,38,39 To confirm the microgravity achieved by this clinostat, we tested the effects of the simulated microgravity on biological characteristics of primary mouse osteoblasts in this experimental condition ( Figure S1).…”
Section: Clinorotation To Simulate Microgravitymentioning
confidence: 99%
“…It was also shown that miR‐133a could hamper bone formation by targeting RUNX2 . MiR‐33, on the other hand, was involved in mechano‐induced osteoblast differentiation, but its association with BMD has yet to be reported.…”
Section: Mirnas In Antiosteoporosis Treatmentmentioning
confidence: 99%